2022
DOI: 10.1055/a-1918-4191
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Electrophilic N-Aryl Intermediates from Aryl Azides, Nitroarenes, and Aryl Amines in Cyclization–Migration Reactions

Abstract: An Account of our development of reactions to construct N-heterocycles by triggering cyclization-migration tandem reactions from aryl azides, nitroarenes, and aryl amines is described. The reactivity patterns of metal N-aryl nitrenes, nitrosoarenes, N-aryl nitrogen radical anions, and N-aryl nitrenoids are compared. 1. Introduction 2. Unlocking the reactivity embedded in aryl azides 3. Exploiting the reactivity of nitrosoarenes generated from nitroarenes 4. Radical anion N-aryl nitrogen reactive intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…These results revealed that the reaction course of α-phenyl-vinyl azide and azido-quinones is absolutely different. Also, it has been demonstrated that, unlike α-phenyl-vinyl azides, β-phenyl-vinyl azides bearing electron-withdrawing groups such as ketone/ester at α-position react differently and proceed through the intermediaries of 2 H -azirines . The literature report on the multifaceted reaction of azides , and our comparative experimental observation undoubtedly indicate that the transformation of azido-quinones to p -QBZDs under our reaction condition with and without 1,2-azide-nitrogen migration involves a different and distinct mechanism that prompted us to conduct intensive control experiments to understand the mechanistic pathway.…”
Section: Resultsmentioning
confidence: 69%
“…These results revealed that the reaction course of α-phenyl-vinyl azide and azido-quinones is absolutely different. Also, it has been demonstrated that, unlike α-phenyl-vinyl azides, β-phenyl-vinyl azides bearing electron-withdrawing groups such as ketone/ester at α-position react differently and proceed through the intermediaries of 2 H -azirines . The literature report on the multifaceted reaction of azides , and our comparative experimental observation undoubtedly indicate that the transformation of azido-quinones to p -QBZDs under our reaction condition with and without 1,2-azide-nitrogen migration involves a different and distinct mechanism that prompted us to conduct intensive control experiments to understand the mechanistic pathway.…”
Section: Resultsmentioning
confidence: 69%
“…Our findings are consistent with previously reported data for both catalytic and thermal decomposition . Notably, the Rh(II)-catalyzed cyclization–migration tandem reaction has been comprehensively explored by Driver, who introduced a migratory aptitude scale, ranking substituents in the following order: ester < alkyl < aryl < aminomethylene < amide < H < sulfone < ketone ≪ nitro group . Notably, according to Driver’s migratory aptitude scale, furyl is positioned in close proximity to aryl.…”
Section: Resultsmentioning
confidence: 99%
“…6 Particularly, in 2008, Driver demonstrated that the decomposition of 2-azidostilbenes can be conducted at lower temperatures, with yields of desired indoles approaching quantitative. 7 Furthermore, by employing mild Rh(II)catalyzed decomposition of 2-substituted aryl azides, 8 Driver developed elegant protocols for synthesizing a wide range of diverse azaheterocycles, including carbazoles, 9 carbolines, 10 benzimidazoles, 11 benzisoxazoles, and 2H-pyrazoles. 12 Based on the presently available data on the decomposition of 2-azidostyrenes, we can establish the following well-founded conclusions: (1) regardless of the quantity and nature of substituents at the olefinic moiety, the double C−C bond consistently remains the primary locus of reactivity; (2) this reactivity consistently culminates in the exclusive formation of a pyrrole ring.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroarenes serve as key building blocks and versatile intermediates in synthetic chemistry and are precursors to a range of other academically and industrially relevant molecules, namely anilines, [18–21] aryl azides, [22–24] and aryl diazonium salts (Scheme 1a) [25,26] . Given their prevalence as inexpensive and readily available feedstocks, the development of innovative methodologies employing nitroarenes as the direct nitrogen source is of particular importance [27,28] . A number of reports exploring the reactivity of nitroarenes has been disclosed in recent years, for example, molybdenum, copper or P III /P V ‐catalyzed system for the reductive C−N cross‐coupling of nitroarenes with arylboronic acids, [29–37] nickel‐ or manganese‐catalysed amidation and amination, [38–43] iron‐catalyzed olefin hydroamination, [44] electrophilic amination with organozinc compounds, [45] showcasing the potential for exploiting nitroarene compounds as simple precursors for the design of new atom‐, step‐ and redox‐economical reactions to form value‐added products.…”
Section: Introductionmentioning
confidence: 99%